PERAN KEPOLISIAN DALAM PENEGAKAN HUKUM TERHADAP PEMAKAI DAN PENGEDAR NARKOTIKA DI KABUPATEN MERAUKE - Rudini Hasyim Rado; Mulyadi Alrianto Tajuddin; Andi Baso Kumala (SOL JUSTICIA, 2022)
This study aims to determine the role of the police in law enforcement against narcotics users and dealers in the Merauke Regency and to find out what factors are inhibiting the role of the police in law enforcement of narcotics crimes in Merauke Regency. The research method used is the type of empirical juridical research using the types and sources of primary and secondary data and then arranged descriptively. From the results of the study, it was concluded that: The Drug Investigation Unit can act on and resolve all cases handled by various series of settlement flows that are carried out either openly or using disguised tricks so that there is a decrease in the number of cases from 2018 to 2020 including prevention using facilities non-penal, in addition to the maximum efforts that have been made in the implementation of disclosure of criminal acts of narcotics abuse, the Narcotics Investigation Unit has several obstacles, namely human resources and infrastructure, but there are sources of information that help in efforts to handle cases, namely sources of information from informants or networks